2006
DOI: 10.4049/jimmunol.176.10.5730
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: CD1a+ Antigen-Presenting Cells in Human Dermis Respond Rapidly to CCR7 Ligands

Abstract: Recent data from murine models have confirmed that Langerhans cells are not the only population of APCs in the skin involved in initiating immune responses. In healthy human skin, we identify CD1a+ dermal APCs located close to the lymphatic vessels in the upper layers of the dermis that are unequivocally distinct from migrating Langerhans cells but exhibit both potent allostimulatory capacity and a chemotactic response to CCR7 ligands. In contrast, CD14+ dermal APCs are distributed throughout the dermis and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
125
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(134 citation statements)
references
References 19 publications
(10 reference statements)
8
125
1
Order By: Relevance
“…Dermal dendritic cells are a heterogeneous cell population, both in humans (Nestle et al 1993;Angel et al 2006;Angel et al 2007) and mice (Bursch et al 2007;Ginhoux et al 2007;Poulin et al 2007;Shklovskaya et al 2008). In contrast to LCs, DDCs display an amoeboid morphology (Ng et al 2008a), more characteristic of a migratory cell (Gunzer et al 2000).…”
Section: Dendritic Cells In the Skinmentioning
confidence: 99%
“…Dermal dendritic cells are a heterogeneous cell population, both in humans (Nestle et al 1993;Angel et al 2006;Angel et al 2007) and mice (Bursch et al 2007;Ginhoux et al 2007;Poulin et al 2007;Shklovskaya et al 2008). In contrast to LCs, DDCs display an amoeboid morphology (Ng et al 2008a), more characteristic of a migratory cell (Gunzer et al 2000).…”
Section: Dendritic Cells In the Skinmentioning
confidence: 99%
“…Although we could detect MGL ϩ DC in the emigrated population, their numbers were slightly lower than expected. This can be explained by the DC maturation that accompanies the emigration from skin explants (20). DC maturation abrogates MGL expression and thus reduces the final numbers of DCs that are still MGL positive after completing the emigration from skin (8).…”
Section: Mgl Mediates Retention Of Immature Dcsmentioning
confidence: 99%
“…[2][3][4] In murine models, the precise role of Langerhans cells remains a matter of debate [4][5][6][7][8][9][10] ; in contrast, APCs that have migrated from the murine dermis have been shown to be essential for the initiation of certain T-lymphocyte responses. 2,11 We recently identified a human dermal APC subset capable of migrating in response to lymph node-homing chemokines and stimulating naive CD4 T lymphocytes 12 ; furthermore, a recent study has shown that they also stimulate CD8 T lymphocytes. 13 Given the pivotal role of dermal APCs for the generation of immune responses in mice, we sought to confirm that their putative human counterparts migrate to lymph nodes draining human skin.…”
Section: Introductionmentioning
confidence: 99%